The Effect of Electronic Recordkeeping Implementation in Information Intensive Agency - Norolazmi, Nurzeelawati; Farik Mat Yatin, Saiful; Kamaruddin Abd Kadir, Irwan; Ridwan Seman Kamarulzaman, Mohd; Hussin, Nurussobah; Atiqaf Mahathir, Nur; oyahirah Mohamad Mobin, Noor (International Journal of Engineering and Technology, 2018)
An Electronic Records Management System (ERMS) is a computer-based program that sets up for the retrieval process of the records that stored in the system.  This aim of the study was to investigate the effect of Electronic Recordkeeping implementation in Information Intensive Agency.  The objectives were to determine whether there is a policy in electronic recordkeeping in this agency, to identify whether staff at this agency has skills or knowledge in electronic recordkeeping and to identify the challenges facing the implementation of electronic recordkeeping in this agency.  A case study research method will be adopted to ensure greater reliability of data.  Data will be collected from 40 staff using questionnaires and interview, in order to respond to the above objectives.  Quantitative approaches will be used to analyze, present and interpret data and also supported by some interview from the expert.